Mechanistic insights into interface-facilitated dislocation nucleation and phase transformation at semicoherent bimetal interfaces. (November 2021) - Shen, X.P.; Yao, B.N.; Liu, Z.R.; Legut, D.; Zhang, H.J.; Zhang, R.F.
Highlights: The misfit dislocation patterns of hcp/bcc semicoherent bimetal interfaces with B and PS ORs were characterized. The deformation mechanism of dislocation nucleation and phase transformation is revealed, where the former is closely related to dynamic evolution of misfit dislocation patterns and the latter is correlated to the specific loading mode and interface structure. The phase transformation path for the required atomic rearrangements were revealed. Competition relationship between non-basal dislocation nucleation and phase transformation were revealed via twisted interface models. Abstract: The nucleation of lattice dislocations and interface sliding at bimetal interfaces are two fundamental mechanisms of plasticity that are responsible for the mechanical responses of nanostructured materials; however, the interface-facilitated phase transformation is rarely considered owing to its relatively high energy barrier for activation. Taking the bimetal hcp/bcc interfaces with Pitch-Schrader and Burgers orientation relationships (ORs) as an illustration, we show that both non-basal dislocation nucleation and hcp-to-bcc phase transformation can be activated at the interface under external loading when the basal slip systems are effectively suppressed. The non-basal dislocation nucleation is shown to be closely related to the dynamic evolution of misfit dislocation patterns at the semicoherent interface, in which the 1/6 [ 02 2 ¯ 3 ¯ ] pyramidal dislocation is not strictly parallel to the ( 01 1 ¯ 1 ) stacking fault plane owing to the corrugated feature. In contrast to non-basal dislocation nucleation, phase transformation requires specific crystallographic ORs of the constituent metals under certain loading conditions, which corresponds to the process of alternate shuffle and shear deformation that involves atomistic migration. To further reveal the competition between non-basal dislocation nucleation and phase transformation, a series of twisted interface models were constructed to systematically investigate the optimal condition of the interface geometry for phase transformation. The phase transformation occurred only when the dislocation nucleation was further hindered at some specific twist angles, suggesting a strong dependence of phase transformation on the interface structure. These findings provide a foundation to the atomistic mechanism of various interface-mediated deformation and a solution to tune interface-facilitated plasticity via interface engineering.